Semantic Analysis of Legal Documents in the Memorandum of Understanding (Mou) of The Indonesian Ministry of Health - akrimni, fida rika; Rahayuningsih, Retno (Universitas Nasional, 2024)
The use of language in a MoU requires precision so that the message conveyed can be understood clearly, which ultimately supports the achievement of effective cooperation. By understanding the denotative and connotative meaning, parties entering into cooperation agreements in the business sector can better understand the contents of the MoU document. The research method used in this research is a descriptive method with qualitative data analysis. This research will analyze the denotative meaning and connotative meaning based on three stages of interpretation, namely literal meaning, explicature and implicature. The data source used is the Memorandum of Understanding (MoU) of the Indonesian Ministry of Health, from three different MoUs, namely the Danish MoU, Japan MoU and Tanzania MoU. The results of this research found denotative and connotative meanings in each MoU document. In the Danish MoU research there was 60% Denotative Meaning, 40% Connotative Meaning, while in the Japanese MoU research there was 50% Denotative Meaning, 50% Connotative Meaning, and the results found in the Tanzanian MoU research were 62.5% Denotative Meaning and 37.5% % Connotative Meaning. Of the three Memorandums of Understanding (MoU), the denotative meaning is more dominant than the connotative meaning.